2016
DOI: 10.11138/mltj/2016.6.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of platelet rich plasma and micro-fat in sport and race horses with degenerative joint disease: preliminary clinical study in eight horses

Abstract: SummaryBackground: To assess the safety and potential efficacy of a standardized technique consisting of intra-articular injection of 10 cc of a homogeneous mixed product using autologous micro-fat and platelet rich plasma (PRP) (ratio 1:1) in the carpus or the fetlock joint of sport horses presenting degenerative joint disease (DJD). Methods: Eight sport horses with DJD confirmed by radiography and ultrasonography and causing lameness and the impossibility to compete were treated. PRP was prepared after a dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 24 publications
(24 reference statements)
0
25
0
Order By: Relevance
“…Lameness exams were performed 1 week prior to treatment and each week for 3 weeks and again at 8 weeks following treatment using three forms of evaluation: clinical evaluation, an inertial sensor system (Lameness Locator ® ) and coach evaluations (only performed post‐treatment), with all three forms of evaluation blinded to the others. For clinical evaluation, the horse was hand‐walked in a 10 m straight line, hand‐jogged in a 60 m straight line twice, and hand‐jogged in two 20 m circles to the right and left on a concrete surface, and lameness was scored using the AAEP scoring system . Following clinical evaluation, the same veterinarian supervised data collection for the inertial based sensor system (Lameness Locator ® ).…”
Section: Methodsmentioning
confidence: 99%
“…Lameness exams were performed 1 week prior to treatment and each week for 3 weeks and again at 8 weeks following treatment using three forms of evaluation: clinical evaluation, an inertial sensor system (Lameness Locator ® ) and coach evaluations (only performed post‐treatment), with all three forms of evaluation blinded to the others. For clinical evaluation, the horse was hand‐walked in a 10 m straight line, hand‐jogged in a 60 m straight line twice, and hand‐jogged in two 20 m circles to the right and left on a concrete surface, and lameness was scored using the AAEP scoring system . Following clinical evaluation, the same veterinarian supervised data collection for the inertial based sensor system (Lameness Locator ® ).…”
Section: Methodsmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) is a multifunctional platelet concentrate of the blood that may be used for the treatment of the manifestations of osteoarthritis, including osteonecrosis of the femoral head, cartilage injury and rheumatoid arthritis (10). It has been demonstrated previously that PRP improves the repair of articular cartilage injury in patients with joint disease by removing harmful inflammation factors (11). It was also demonstrated that PRP reduces the level of inflammatory factor synovial fluid in rheumatoid arthritis without exhibiting side effects (12).…”
Section: Introductionmentioning
confidence: 99%
“…We previously described the safety profile of combining autologous microfat and PRP as a mixed regenerative product injected in the carpus or the fetlock joint of sport horses presenting with degenerative joint disease [ 25 ]. A significant lameness reduction, together with an early return to compete were also indicative of potential efficacy.…”
Section: Introductionmentioning
confidence: 99%